2020
DOI: 10.1186/s43054-019-0016-4
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effect of adenotonsillectomy on growth and nutritional anthropometric parameters of children with obstructive adenotonsillar enlargement

Abstract: Background: Obstructive adenotonsillar enlargement is known to cause failure to thrive in children. The effect of adenotonsillectomy is not well documented on the growth of affected children. The study was carried out to investigate the effect of adenotonsillectomy on growth of children with obstructive adenotonsillar enlargement. It was a quasi-experimental study consisting of 62 children (≤ 12 years) with obstructive adenotonsillar enlargement and 62 healthy controls. Variables measured at baseline, sixth we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 38 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…(1) Studies with population of children aged 18 years and below with polysomnographically diagnosed OSA, (2) Full-text studies, (3) Administration of adenotonsillectomy, (4) Clinical studies that reported changes in serum biomarkers after soft-tissue surgery for OSA, (5) published in a peer-reviewed journal, and (6) written in English. Exclusion criteria were (1) Case reports, reviews, or letters, (2) Abstracts or conference proceedings, (3) no pre-and post-operative comparisons for biochemical markers, (4) OSA diagnosed based on clinical history or questionnaires only, that is, not polysomnographically diagnosed OSA, (5) Adenotonsillar hypertrophy or snoring without OSA, (6) No distinction between results from non-surgical and surgical interventions, and (7) Not a serum biomarker.…”
Section: Search Strategy and Selection Criteriamentioning
confidence: 99%
See 2 more Smart Citations
“…(1) Studies with population of children aged 18 years and below with polysomnographically diagnosed OSA, (2) Full-text studies, (3) Administration of adenotonsillectomy, (4) Clinical studies that reported changes in serum biomarkers after soft-tissue surgery for OSA, (5) published in a peer-reviewed journal, and (6) written in English. Exclusion criteria were (1) Case reports, reviews, or letters, (2) Abstracts or conference proceedings, (3) no pre-and post-operative comparisons for biochemical markers, (4) OSA diagnosed based on clinical history or questionnaires only, that is, not polysomnographically diagnosed OSA, (5) Adenotonsillar hypertrophy or snoring without OSA, (6) No distinction between results from non-surgical and surgical interventions, and (7) Not a serum biomarker.…”
Section: Search Strategy and Selection Criteriamentioning
confidence: 99%
“…2 Left untreated, this poses significant cardiovascular risks, 3,4 and predisposes children to metabolic disorders. 5 Furthermore, it may impede childhood development and growth 6 and leads to neurocognitive issues such as impaired attention and memory, hyperactivity, poor academic performance, and even psychiatric problems like depression. [7][8][9] Particularly, untreated severe OSA is a contributor to cardiovascular morbidity in children and has been demonstrated to cause bi-ventricular dysfunction, 10 blood pressure lability, 11 and endothelial dysfunction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with, obstructive sleep disorder, snoring, persistent rhinorrhea, as well as hyponasal speech, nasal blockage is one of the main symptoms they come with. Hyperplastic adenoids, on the other hand, can be colonized by bacteria and may serve as a source of chronic illness (1,2) . Obstruction of the upper airway, particularly during sleep, can cause distress to the respiratory system and a host of related problems.…”
Section: Introductionmentioning
confidence: 99%